Metode Simple Additive Weighting Dalam Pemilihan Karyawan Berprestasi Pada PT. Kereta Commuter Indonesia Stasiun Rawa Buntu - Utami, Yuliantika Siswanti; Ramanda, Kresna (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2020)
Rawa Buntu Indonesia Commuter Train Station has its own qualifications in selecting employees, as well as in determining employees who excel. This study aims to give awards to employees who excel. Through this award every employee is expected to be motivated to become better and improve quality. The problem faced is the difficulty in determining who is chosen to be an outstanding employee with subjective criteria. To overcome this problem, a decision support system is designed for the selection of outstanding employees using the SAW Method. By using 5 different variables, namely Integrity, Cooperation, Communication, Quality of Work and Work Discipline. By applying the Simple Additive Weighting (SAW) method, the process of selecting employee performance is more efficient so that the station can make decisions more quickly for employees who excel. Decision making system using the Simple Additive Weighting (SAW) method has helped the station in determining the selection of employee performance.